2005
DOI: 10.1002/mame.200500080
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Behavior and Complex Formation Ability of Ternary Amphoteric Gels based on Allylamine Derivatives and Maleic Acid

Abstract: Summary: The swelling behavior of an amphoteric gel composed of 50 mol‐% of maleic acid (MA), 25 mol‐% of N,N′‐dimethyldiallylammonium chloride (DMDAAC) and 25 mol‐% of diallylamine (DAA) was studied in aqueous and aqueous‐salt solutions. The isoelectric point (IEP) of the MA‐DMDAAC‐DAA gel determined from swelling experiments was about pH 4.6. Considerable gel swelling with increasing ionic strength was observed at the IEP. Dynamic swelling properties of the amphoteric gel in water with and without added salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The swelling reaches 64 g/g in 0.9% NaCl solution for hydrogel with 30 mL AA of feed composition. However, no obvious polyampholyte behaviors were observed among three polymer hydrogels 25. This may be because the added salt may not break the interchain association so easily, or because the polymer gels mainly show anionic property because cationic groups in the starch is in a small fraction compared with anionic groups.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The swelling reaches 64 g/g in 0.9% NaCl solution for hydrogel with 30 mL AA of feed composition. However, no obvious polyampholyte behaviors were observed among three polymer hydrogels 25. This may be because the added salt may not break the interchain association so easily, or because the polymer gels mainly show anionic property because cationic groups in the starch is in a small fraction compared with anionic groups.…”
Section: Resultsmentioning
confidence: 88%
“…It can be concluded that water transport is controlled by polymer relaxation process. In the case of amphoteric gels, the polymer relaxation is significantly affected by the ionization degree of the functional groups 25. The electrostatic repulsion between adjacent carboxyl groups or ammonium groups leads to macromolecular chain expansion, making the mechanism more relaxation‐controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Kudaibergenov et al21 studied the behavior of amphoteric hydrogels based on vinyl 2‐aminoethyl ether and sodium acrylate under the influence of the pH, ionic and solvent compositions, temperature, and electric field. With good biocompatibility and peculiar characteristic, amphoteric, absorbent polymers are applied to the therapy of cardiovascular diseases,22 intelligent materials,23 and the controlled release of drugs 24…”
Section: Introductionmentioning
confidence: 99%
“…The swelling–deswelling behavior of amphoteric gel which was made of maleic acid (MA), N , N ’-dimehyldiallylammonium chloride (DMDAAC) and diallylamine (DAA) was studied in the presence of NaPSS [133]. The swelling degree of the amphoteric gel–NaPSS is minimally in the pH range between 4 and 8 (Figure 13) and increases significantly in the strong acidic and alkaline regions.…”
Section: Interpolyelectrolyte Complexes Of Polyampholytesmentioning
confidence: 99%
“…pH dependent swelling of amphoteric gel MA-DMDAAC-DAA (1) and complexes of amphoteric gel with NaPSS (2). (Updated from [133]).…”
Section: Figures Schemes and Tablesmentioning
confidence: 99%